Creative success in teams - McKay, Alexander S.; Reiter-Palmon, Roni, 1964-; Kaufman, James C. (Explorations in creativity research., 2021)
"Today's workers spend upwards of 80% of their time collaborating and teams have become the fundamental unit within organizations. Creative Success in Teams summarizes for practitioners and researchers what drives team creativity. Utilizing research from psychology, organizational behavior/management, business, and education, the book discusses how best to start, manage, and foster creativity in team environments, how to encourage participation and collaboration, what makes for the most creative team, and how best to lead and evaluate creative teams"--